2004
DOI: 10.1519/1533-4287(2004)18<625:saahrt>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Strength Adaptations and Hormonal Responses to Resistance Training and Detraining in Preadolescent Males

Abstract: Nineteen untrained preadolescent males (11-13 years old) were randomly placed into an experimental trained group (STG, n = 9) and a control group (n = 10). Informed consent was obtained from the children and their parents. The STG was submitted to a 2-month resistance-training program (6 exercises, 3 x 10 repetitions maximum [RM], 3 times per week), followed by a 2-month detraining program. The effectiveness of the resistance program was determined by measuring pre- and posttraining and detraining differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 21 publications
1
30
0
4
Order By: Relevance
“…While some studies demonstrate an increase in the resting levels of testosterone as an adjustment to ST (Izquierdo et al, 2006;Kraemer et al, 1995;Nicklas et al, 1995;Raastad et al, 2003;Tsolakis et al, 2004), other studies have observed no significant differences in this parameter (Ahtiainen et al, 2003;Hansen et al, 2001;Hickson et al, 1994). So far, available data indicate that only young individuals are capable of altering their resting hormone concentrations (Häkkinen et al, 1988;Staron et al, 1994;Tsolakis et al, 2004), whereas middle-aged and elderly individuals show no significant changes in such parameters (Häkkinen & Pakarinen, 1994;Häkkinen et al, 2000;2001a;Izquierdo et al, 2006;Ryan et al, 1994).…”
Section: Chronic Endocrine Adaptations To Physical Training 41 Basalmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies demonstrate an increase in the resting levels of testosterone as an adjustment to ST (Izquierdo et al, 2006;Kraemer et al, 1995;Nicklas et al, 1995;Raastad et al, 2003;Tsolakis et al, 2004), other studies have observed no significant differences in this parameter (Ahtiainen et al, 2003;Hansen et al, 2001;Hickson et al, 1994). So far, available data indicate that only young individuals are capable of altering their resting hormone concentrations (Häkkinen et al, 1988;Staron et al, 1994;Tsolakis et al, 2004), whereas middle-aged and elderly individuals show no significant changes in such parameters (Häkkinen & Pakarinen, 1994;Häkkinen et al, 2000;2001a;Izquierdo et al, 2006;Ryan et al, 1994).…”
Section: Chronic Endocrine Adaptations To Physical Training 41 Basalmentioning
confidence: 99%
“…So far, available data indicate that only young individuals are capable of altering their resting hormone concentrations (Häkkinen et al, 1988;Staron et al, 1994;Tsolakis et al, 2004), whereas middle-aged and elderly individuals show no significant changes in such parameters (Häkkinen & Pakarinen, 1994;Häkkinen et al, 2000;2001a;Izquierdo et al, 2006;Ryan et al, 1994). Increases in resting levels of testosterone seem to occur during periods of highvolume (Kramer et al, 1995;Marx et al, 2001) and high-intensity training (Staron et al, 1994;Kraemer et al, 1998;Raastad et al, 2003).…”
Section: Chronic Endocrine Adaptations To Physical Training 41 Basalmentioning
confidence: 99%
“…10 Information regarding the effects of detraining on younger populations is scarce and results have been controversial. [11][12][13][14] In the case of adults, the situation is similar, with negative effects on lipid metabolism 15 or no changes at all. 16,17 In this context, the objective of this study was to assess the effects of detraining (cessation of scheduled physical exercise) on the lipid profile (HDL, LDL, total cholesterol [TC] and TG) of obese children.…”
Section: Introductionmentioning
confidence: 99%
“…10 La información relativa sobre los efectos del desentrenamiento en las poblaciones más jóvenes no es muy amplia y muestra resultados contradictorios. [11][12][13][14] Por su parte, en los adultos, ocurre algo similar y se muestran efectos negativos sobre el metabolismo lipídico 15 o no se observan cambios al respecto. 16,17 En este contexto, el objetivo del presente estudio fue evaluar los efectos del desentrenamiento (cese del ejercicio físico programado) sobre el perfil lipídico (HDL, LDL, CT y TG) en niños obesos.…”
Section: Introductionunclassified